Design of microstrip patch antenna arrays at 10 GHz / Harith Yussof - Yussof, Harith (2006)
The purpose of this project is to design microstrip patch antenna arrays with operating or resonant frequency at approximately 10 GHz. The voltage standing wave ratio (VSWR) should be less than 2 at the resonant frequency. The microstrip patch antenna arrays are the upgrade version of past semester's final project The main parameters concerned for this project are retum loss Sn and VSWR. For the simulation, HP EEsofUBRA Computer aided design (CAD) simulation package is used to determine the simulated response of the arrays.